Rheologic and shape memory properties of natural biopolymers - Muhammad Nor Arifin, Yaakob; Rasidi, Roslan; Mohd Hasbi, Ab Rahim (Elsevier, 2024)
The development of shape memory polymers (SMPs) with unique structures and characteristics has attracted sudden interest from both industries and academia. Numerous raw materials have been used to develop SMPs, particularly involving biobased or natural biopolymers, owing to concerns about sustainability and environmental issues. To overcome the limitations of synthetic SMPs, the development of novel biobased materials is necessarily has created great scientific and technological interest. Therefore, this chapter primarily focuses on natural biopolymer SMPs (NBSMPs) produced using biobased raw materials. The chapter emphasizes progress made on NBSMPs by countless researchers worldwide. A discussion and elaboration of the rheology concept, principals, rheologic investigation, shape fixing, and recovery of NBSMPs are highlighted. Applications of NBSMPs in the aerospace, biomedical, soft robotics, and intelligent fabric industries are provided. Finally, a summary and the future outlook of NBSMPs are presented.